Digital Crisis Governance: A Systematic Study of Government Crisis Communication in The Social Media Era (2020–2025) - Judika Margaretha (Eduvest - Journal of Universal Studies, 2026)
This study employs a Systematic Literature Review (SLR) approach guided by the PRISMA framework, with literature curated from the Scopus database covering the 2020–2025 period. The synthesis of 28 selected articles reveals three main findings. First, government crisis communication is evolving from a reactive model to a proactive and sustainable one, aligning with the Ongoing Crisis Communication (OCC) framework, which emphasizes pre-, during-, and post-crisis communication as integral elements of the governance process. Second, the effectiveness of digital crisis communication is primarily determined by the configuration of speed, accuracy, empathy, message consistency, and “adaptive transparency”—a concept that considers public literacy and the audience’s psychological state—as formulated in the CERC model and supported by empirical findings across multiple platforms (Twitter, Instagram, Facebook, Weibo). Third, recent studies underscore that public trust is not built merely through data transparency but also through perceptions of the government’s goodwill, integrity, and capacity to manage collective emotions (affective publics), as well as collaboration with external actors such as independent media, fact-checkers, and citizen journalists to counter disinformation. Moreover, the political and cultural context moderates the success of communication strategies: authoritarian regimes tend to excel in speed and message consistency but are limited in substantive participation, whereas democracies often grapple with polarization and legitimacy contestation. This study concludes that government crisis communication in the digital era should be understood as digital crisis governance—an integrated process combining adaptive transparency, strategic empathy, and cross-actor collaboration to strengthen legitimacy and public trust sustainably.